MENEMUKAN KETENANGAN DI TENGAH BADAI KECEMASAN: PENDEKATAN KONSELING ISLAM - Jannah, Miftahul; Nurjannah (Counseling For All : Jurnal Bimbingan dan Konseling, 2025)
The purpose of this study is to explore the effectiveness of Islamic counseling methods in reducing individual levels of anxiety and to understand how spiritual elements in Islam—such as tawakkul (trust in God), dhikr (remembrance of God), and shalat (prayer)—can serve as therapeutic tools. This research also aims to provide new insights for counselors, especially those working within Muslim communities, on how to integrate religious values into counseling practices. With a holistic approach, Islamic counseling is expected to offer an effective alternative in helping individuals cope with anxiety comprehensively, addressing both psychological and spiritual dimensions. Anxiety is one of the most common psychological issues experienced by people across different societal backgrounds. Contributing factors such as social pressure, economic stress, and high self-expectations often trigger anxiety. This study focuses on how Islamic counseling methods can provide peace and tranquility to individuals experiencing anxiety. The article investigates the core principles of Islamic counseling, emphasizing spiritual understanding, prayer, and the human relationship with God as sources of inner calm. The findings indicate that the Islamic approach not only addresses psychological aspects but also offers deeper meaning by strengthening religious faith as a foundation for emotional peace.